Sin and Evil in Feminist Thought - Smith, Christine M. (Theology today, 1993)
“Praxis is central to feminist thought and theology. It is not enough simply to speak or to write about sin and evil if our theologies do not lead to change and transformation. Feminist theology takes as its starting point concrete human suffering and oppression and, then, builds theologies in response to that human reality.”